All Days 2013
DOI: 10.2523/iptc-17010-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fractured Well Performance in Naturally Fractured Reservoirs

Abstract: Multiple hydraulic fracture treatments in the reservoirs with natural fractures create complex fracture networks. Predicting well performance in such a complex fracture network system is an extreme challenge. The statistical nature of natural fracture networks changes the flow characteristics from that of a single linear fracture. Simply using single linear fracture model for individual fractures, and then summing the flow from each fracture as the total flow rate for the network could introduce a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To overcome these shortages, Lin and Zhu (2012) and Hwang et al (2013) applied semi-analytical methods to estimate the performance of HWFN. In these studies, each HF was connected to the wellbore, and MF was connected to HF.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortages, Lin and Zhu (2012) and Hwang et al (2013) applied semi-analytical methods to estimate the performance of HWFN. In these studies, each HF was connected to the wellbore, and MF was connected to HF.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, semi-analytical methods (Chen and Raghavan, 1997; Ezulike and Dehghanpour, 2014a, 2014b; Guo and Evans, 1993) are introduced to study the transient pressure in complex fracture networks. Lin et al (2012) and Hwang et al (2013) predicted the performance of the fractured horizontal well with fracture networks by semi-analytical method. However, the finite fracture conductivity of the horizontal well is not taken into consideration in the model, leading to unreliable results.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested the fractal discrete fracture network (FDFN) model, which incorporates the various scale-dependent data, such as outcrops, logs, and cores, and creates more realistic natural fracture networks. This FDFN model is combined with the slab source model to build fracture networks first, and then the flow problem in the complex fracture systems is solved . However, the choice by Hwang el al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have worked on forecasting the production from fractured wells. Hwang et al 24 introduced a method that addresses the problem of having natural fractures, which is only one element of heterogeneity, by considering the fractures as a combined series of slab sources and superposing the sources under several boundary or flow conditions. They claimed that, to reflect the heterogeneous nature of natural fractures, a stochastic method of generating discrete fracture networks should be adopted.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation